Introduction to special issue: Attention & Plasticity. Issue 2 (3rd April 2017) - Hopfinger, Joseph B.
ABSTRACT: Mechanisms of attention are a prime target for investigating the plasticity of the adult brain, as these core mechanisms act at the intersection of top-down and bottom-up processing, and the wide variety of methods used in attention research can be utilized to elucidate the mechanisms of plasticity. This special issue of Cognitive Neuroscience presents three new empirical papers and a discussion paper with peer commentaries. In the first article, Voelker, Sheese, and colleagues investigate the influence of genetic variation on the effectiveness of attention training. Della Libera and colleagues then present a study investigating how individual differences in personality traits affect the acquisition of reward-based attention biases. In the final empirical paper, Hopfinger and colleagues present a transcranial stimulation study investigating the influence of different oscillatory stimulations on the efficiency of attentional reorienting. Finally, Voelker, Piscopo, and colleagues present a discussion paper in which they suggest that successful training of attention is linked to changes in the underlying white matter. The papers in this special issue present a sampling of the range of issues and methodologies being brought to bear to further our understanding of the malleability of the mechanisms of attention and of the plasticity of the brain.